2012
DOI: 10.1021/jm3005866
|View full text |Cite
|
Sign up to set email alerts
|

The Discovery and Optimization of a Novel Class of Potent, Selective, and Orally Bioavailable Anaplastic Lymphoma Kinase (ALK) Inhibitors with Potential Utility for the Treatment of Cancer

Abstract: A class of 2-acyliminobenzimidazoles has been developed as potent and selective inhibitors of anaplastic lymphoma kinase (ALK). Structure based design facilitated the rapid development of structure-activity relationships (SAR) and the optimization of kinase selectivity. Introduction of an optimally placed polar substituent was key to solving issues of metabolic stability and led to the development of potent, selective, orally bioavailable ALK inhibitors. Compound 49 achieved substantial tumor regression in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 16 publications
1
51
0
Order By: Relevance
“…Although this decrease in hydrolysis was attributed to steric hindrance, electronic effects may also be implicated since substantial decrease in hydrolysis may also be achieved by parasubstitution (Testa and Mayer, 2003). In the case of the ALK inhibitors described here, ortho-substitution was not tolerated, most likely due to the distortion of the coplanar conformation that was required for an optimum interaction with the ALK protein (Lewis et al, 2012). Studies of meta-or para-substitution on the benzamide moiety demonstrated a clear structure activity relationship.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Although this decrease in hydrolysis was attributed to steric hindrance, electronic effects may also be implicated since substantial decrease in hydrolysis may also be achieved by parasubstitution (Testa and Mayer, 2003). In the case of the ALK inhibitors described here, ortho-substitution was not tolerated, most likely due to the distortion of the coplanar conformation that was required for an optimum interaction with the ALK protein (Lewis et al, 2012). Studies of meta-or para-substitution on the benzamide moiety demonstrated a clear structure activity relationship.…”
Section: Discussionmentioning
confidence: 85%
“…All fresh plasma and blood were obtained from the in vivo group at Amgen. All proprietary ALK inhibitors were synthesized by the Department of Medicinal Chemistry at Amgen (Cambridge, MA) and all synthetic routes have already been published elsewhere (Lewis et al, 2012). All other chemicals were purchased from Sigma-Aldrich (Milwaukee, WI) unless otherwise specified Determination of Stability or CL int in Plasma.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The exception is CH5424802, which binds in a more linear fashion to the hinge region of ALK and extends further back into the pocket adjacent to gatekeeper residue Leu 1196 . Both types of inhibitors display exquisite potency on ALK and a third class of molecules combining elements of both of the first two classes produces another type of potent, selective ALK inhibitor (60). Importantly, the contour of the portion of the ATP site into which these inhibitors bind is not affected in the F1174L or R1275Q neuroblastoma mutants, as described above, nor is it expected to be perturbed upon ALK kinase domain phosphorylation.…”
Section: Discussionmentioning
confidence: 93%